RELEVANSI PERILAKU KONSUMSI PANGAN DALAM UPAYA MENCAPAI KEDAULATAN PANGAN KELUARGA TANI BERBASIS KEARIFAN LOKAL - Muyana, Eka; Sriati, Sriati; Yamin, M.; Yunita, Yunita (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
The purpose of this study was to analyze the relevance of food consumer behavior in an effort to achieve food sovereignty for farming families based on local wisdom in the management of swamp swamps in Kab. OganKomeringIlir, South Sumatra. The sampling method used in this study uses a purposive sampling method. There is a significant relevance between local wisdom and efforts to realize sustainable food sovereignty in Bangsal Village, meaning that food sovereignty is realized because of local wisdom that has been carried out for years which is still being applied by most of the swamp lebak farmers in Bangsal Village. Based on the results of field research that has been discussed and analyzed, it can be concluded that the management of lebak swamp land in Bangsal Village is used for three activities, namely buffalo farming, fish management, and rice cultivation.